Comparative Study of the Prevalence of Psychological and Physiological Symptoms of Pre-Menstrual Syndrome between Rural and Urban Adolescent School-Going Girls - Goswami, Shambaditya; Jain, Arjav; Suman, Supriya; Pathak, Soumya; Pal, Nikita; Singh, Ravindra Pal (Indian Journal of Pharmacy Practice)
Objectives: Premenstrual Syndrome (PMS) is the most common and significant public health issue among younger adults. The main purpose of the study was to compare the prevalence of physiological and psychological symptoms of PMS among adolescent girls in urban and rural areas of Tripura. Materials and Methods: A descriptive cross-sectional survey-based study was carried out in urban and rural schools at Teliamura, Khowai Tripura. 12-18 years old adolescent school-going girls were asked to complete a self-developed questionnaire made according to the ACOG diagnostic criteria for PMS. The questionnaire consisted of information regarding the socio-demographic profile and details of psychological and physiological symptoms. All the data were recorded prospectively. Results: Among 217 girls, 60.8% were diagnosed with PMS as per the ACOG diagnostic criteria of which 66 students belonged to urban areas and the other 66 students were from rural areas. The most common physical and psychological symptoms found in urban and rural area girls were abdominal pain/muscle cramps (100% and 84.8%) and fatigue (92.4% and 65.2%) respectively. Conclusion: The prevalence of both psychological and physical symptoms of PMS in urban area school girls was found to be higher than the rural area girls.
Keywords: Adolescent girls; Physical symptoms; Premenstrual Syndrome; prevalence; Psychological symptoms